2016
DOI: 10.1371/journal.pone.0162162
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Metabolism, Pharmacokinetics and In Vivo Analysis of New Blood-Brain-Barrier Penetrant Fingolimod Analogues: FTY720-C2 and FTY720-Mitoxy

Abstract: Parkinson’s disease (PD) is a neurodegenerative aging disorder in which postmortem PD brain exhibits neuroinflammation, as well as synucleinopathy-associated protein phosphatase 2A (PP2A) enzymatic activity loss. Based on our translational research, we began evaluating the PD-repurposing-potential of an anti-inflammatory, neuroprotective, and PP2A stimulatory oral drug that is FDA-approved for multiple sclerosis, FTY720 (fingolimod, Gilenya®). We also designed two new FTY720 analogues, FTY720-C2 and FTY720-Mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…-During in vitro metabolic stability testing, systems based on different preclinical species are employed (i.e., human, mouse, rat, dog and monkey). As different model organisms are used in the experiments, interspecies variations in metabolic stability are typically observed (9,30,38,(94)(95)(96)(97)(98).…”
Section: In Vitro-in Vivo Extrapolationmentioning
confidence: 99%
See 1 more Smart Citation
“…-During in vitro metabolic stability testing, systems based on different preclinical species are employed (i.e., human, mouse, rat, dog and monkey). As different model organisms are used in the experiments, interspecies variations in metabolic stability are typically observed (9,30,38,(94)(95)(96)(97)(98).…”
Section: In Vitro-in Vivo Extrapolationmentioning
confidence: 99%
“…Enoru et al (97) assessed the preclinical metabolism of new blood-brain-barrier penetrant fingolimod analogues: FTY720-C2 and FTY720-Mitoxy. The in vitro intrinsic clearance of FTY720-C2 was low in dog, moderate in mouse, monkey and human, and high in rat, whereas in the case of the second analogue, FTY720-Mitoxy, the intrinsic clearance was found to be low in mouse, rat and dog, moderate in human and high in monkey.…”
Section: In Vitro-in Vivo Extrapolationmentioning
confidence: 99%
“…We showed that FTY720 improves GI physiology/function and reduces GI aSyn pathology in A53T Tg parkinsonian mice [22]. In CNP-aSyn MSA mice we have assessed FTY720-Mitoxy, our novel neuroprotective FTY720derivative, [27] that though not orally bioavailable, readily crosses the blood brain barrier [31], stimulates trophic factor expression in neurons and oligodendroglia [32,33], and is not immunosuppressive by decreasing circulating T cells [34]. Preliminary data confirm the restorative effects of FTY720-Mitoxy on motor, sudomotor, and GI function in Tg CNP-aSyn MSA mice [21].…”
Section: Introductionmentioning
confidence: 99%
“…In aging aSyn transgenic mice given long term oral FTY720, the mice had reduced aSyn pathology and increased levels of the protective molecule, brain derived neurotrophic factor (BDNF) (Vidal-Martinez et al, 2016). In collaboration with medicinal chemists, we made two non-immunosuppressive FTY720s that also enhance PP2Ac activity, and BDNF expression (Vargas-Medrano et al, 2014; Enoru et al, 2016; Segura-Ulate et al, 2017a). FTY720 and our novel FTY720-based-derivatives, may thus have therapeutic potential for both diabetes and PD.…”
mentioning
confidence: 99%